Biosynthesis of ZnO Nanoparticles from Cnidoscolus aconitifolius Leaf Extract: Structure, Morphology, and Photocatalytic Performance for Methylene Blue and Methyl Orange Degradation by UV Light Irradiation - Sri Wahyu Suciyati; Anisatul Mahmudah; Lusia Prastica; Ayu Aprilia (Jurnal Kimia Sains dan Aplikasi, 2025)
Zinc oxide nanoparticles (ZnO NPs) were produced via an environmentally friendly approach using Cnidoscolus aconitifolius leaf extract and subsequently heat-treated at 250°C. The presence of Zn–O vibrations and organic functional groups in the extract was verified by FTIR analysis, while XRD data revealed a wurtzite structure with a mean crystallite dimension of 17.64 nm. SEM images mainly showed round-shaped particles with a band gap energy of 3.29 eV. Assessments of photocatalytic capability indicated substantial degradation of methylene blue (MB, reaching 92.96%), in contrast to diminished degradation of methyl orange (MO, registering 43.93%). This improved effectiveness was attributed to the combined favorable effects of concurrent photocatalytic processes. The kinetic evaluation followed a pseudo-second-order model, yielding rate constants of 0.38 min−1 for MB and 0.064 min−1 for MO. Overall, the green-synthesized ZnO NPs calcined at 250°C exhibit excellent photocatalytic activity, particularly for the degradation of MB.